Liberia Early Years Policy Note 2018 - World Bank (World Bank, Washington, DC, 2019)
Investment in young children in Liberia is a critical aspect to Liberia's development agenda. While progress is being made, greater momentum is needed to ensure that young children develop and thrive along physical, cognitive, language and socio-emotional dimensions. The quality and quantity of early experiences in the first thousand days lay the foundation for children's brain development, which includes good nutrition, early stimulation, and safe and secure environments. Healthy brains in turn influence health and education outcomes in subsequent years which translates into economic growth. Investments in early experiences yield better health, better school readiness, and higher academic performance which in turn leads to higher economic productivity. The pathway to early childhood development (ECD) starts in utero, therefore, investments in pre-natal services and healthy pregnancies are the starting points to healthy childhoods and productive adulthood. Investment in the early years is a proven gateway to a country's economic growth and development. To reap full benefits of ECD investments, it is critical to start early and integrate programs across health, nutrition, education, and social or child protection sectors. Over the past three decades, Liberia made some improvements in the well-being of the youngest in the country. Despite progress, coverage of services remains low across the ECD continuum from conception through birth to child health and pre-school packages. To conclude, existing guidelines for center or facility-based delivery of ECD services should be reviewed and revised to ensure integration of services.